Investigation of apnea turn at butterfly and breast stroke race - Kishimoto, T.; Takeda, T.; Sugimoto, S.; Takagi, H.; Tsubakimoto, S. (Japanese Journal of Sciences in Swimming and Water Exercise, 2008)
The purpose of this study was to clarify a characteristic of "Apnea Turn" which is a new turning method under water and to compare with a conventional turning method, "Open Turn". The subjects were elite competitive swimmers (n=10), whose specialties were butterfly and breast stroke. The turn phase was defined as a section from 5m front the wall and 5m after the wall. As results, the time of turn phase revealed that Apnea Turn tends to be shorter than Open Turn (5.55± 0.27s and 5.62±0.33s respectively). The time of turn -in- phase and turn -out- phase of turn phase in Apnea Turn was shorter than Open Turn, but pivot phase was significantly longer than Open Turn. The push-off velocity of Apnea Turn was higher than Open Turn significantly (p<0.01). These results suggest that Apnea Turn will be able to contribute to improve the swimming performance and then it may become prospective a new turning method. Therefore, this Apnea Turn will be a new turning method. For future studies, it is important to investigate the motion of pivot and to reduction in pivot phase.